2021
DOI: 10.4103/jpbs.jpbs_801_20
|View full text |Cite
|
Sign up to set email alerts
|

Molar Incisor Hypomineralization: Clinical Characteristics with Special Emphasis on Etiological Criteria

Abstract: Molar incisor hypomineralization (MIH) is an entity to describe the enamel defects of the first permanent molars with the involvement of one or more incisors due to an underlying systemic cause. It is a frequently encountered challenge by dentists in a dental clinic and dental complications affecting patient's quality of life. Early diagnosis is the key to protect and prevent the deterioration of the condition. This article aims to highlight different aspects of etiology to treatment options in young patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The current review considered studies in which PP had been performed for deep carious lesions (ICDAS 4, 5, 6) and post-eruptive breakdown, as the latter is often superimposed on a carious lesion, such as in cases of severe MIH [ 37 ]. The site of exposure of the tooth could influence the success rate [ 40 ]; more failures have been found with axial than occlusal exposures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current review considered studies in which PP had been performed for deep carious lesions (ICDAS 4, 5, 6) and post-eruptive breakdown, as the latter is often superimposed on a carious lesion, such as in cases of severe MIH [ 37 ]. The site of exposure of the tooth could influence the success rate [ 40 ]; more failures have been found with axial than occlusal exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Al-batayneh et al, 2022 [6] Eur Arch Paed Dent Jordan University grant Chailertvanitkul et al, 2014 [3] Int Endod J Thailand Not reported Özgür et al, 2017 [37] BMC Oral Health Turkey University grant Tozar and Erkmen Almaz, 2020 [38] J Endod Turkey University grant Uesrichai et al, 2019 [39] Int Endod J Thailand University grant Uyar and Alacam, 2021 [40] Niger J Clin Pract Turkey None…”
mentioning
confidence: 99%
“…The therapeutic approach should be individualized based on the severity of MIH, patient needs, and available treatment options. Prevention and early diagnosis are paramount to ensuring effective treatment and minimizing complications associated with MIH [1,41,[64][65][66].…”
Section: Icdas IIImentioning
confidence: 99%
“…Clinically patients complain on: ➢ Breakdown: post-eruptive enamel breaks lead to dentine exposure [10].…”
mentioning
confidence: 99%